A Comprehensive Literature Review Investigating the Potential and Constraints Faced by Investors and Developers in Real Estate Investment Trusts (REITs) (Journal of Informatics Education and Research, 2025)
The Indian real estate sector has traditionally relied on informal and fragmented funding channels, resulting in liquidity constraints and limited investor participation. Globally, Real Estate Investment Trusts (REITs) have emerged as innovative investment vehicles providing diversification, transparency, and stable income. In India, however, REIT adoption has been gradual, with regulatory, taxation, and awareness barriers slowing their expansion since their formal introduction in 2014 by SEBI. This study investigates the challenges and prospects of REITs in India, drawing insights from secondary data and existing scholarship. The analysis underscores the transformative potential of REITs in institutionalizing real estate funding, reducing developer debt, and attracting global capital. Findings highlight gaps in regulatory clarity, taxation policy, and investor awareness as critical barriers, while opportunities lie in urbanization-driven demand, foreign direct investment inflows, and SEBI’s evolving regulatory framework. The paper suggests a multi-stakeholder approach involving policymakers, regulators, and investors to unlock REITs’ full potential in India’s real estate sector.